DISEÑO DE MANUAL DE ESTRATEGIAS EN LOS PROCESOS DE CARTERA EN EL FONDO DE EMPLEADOS SOLCRECER DE LA CIUDAD DE SANTA MARTA - CARDENAS PINTO, DANIELA LUCIA; CHAVEZ BAENA, DANIELA LEONOR (Universidad Antonio Nariño, 2023)
With this project, it is proposed to design a manual of strategies in the portfolio processes of the SOLCRECER Employee Fund of the city of Santa Marta. Strengthening the fund with new lines of credit and creating strategies for the recovery of the portfolio of difficult collection, offering the company different options of lines of credit for the benefit of the associates, and likewise implementing debtors insurance so that the fund has greater support when granting loans to associates. An improvement plan was sought, expanded in the interest tables that are currently available, in order to be able to implement new lines of credit with an interest rate lower than the existing one and likewise a debtor insurance so that when making credits, both the associate and the fund have a backup in case they cannot continue discovering their payments for some reason.